Halitosis associated volatiles in breath of healthy subjects - van den Velde, Sandra; Quirynen, Marc; Van hee, Paul; van Steenberghe, Daniel (Journal of chromatography. B, Analytical technologies in the biomedical and life sciences, 2007)
Halitosis can have an intra- or extra-oral origin. In all cases, bad breath is caused by the presence of volatile organic compounds originating from the mouth or the expired air. They can be specific for certain diseases or infections. This study explored the presence and concentration of these volatile compounds normally associated with halitosis in the breath of healthy symptomless volunteers. Alveolar and mouth air of 40 healthy volunteers as well as environmental air were analyzed by gas chromatography–mass spectrometry (GC–MS) and by a commercially available GC device (OralChroma®). 14 compounds, associated with halitosis could be detected. All of them except carbon disulfide, appeared to be (partly) produced endogenously and/or in the mouth. Acetone, 2-butanone, 2-pentanone and 1-propanol were common to all volunteers in both alveolar and mouth air and indole and dimethyl selenide in alveolar air. GC–MS seems a promising tool for differential diagnosis of halitosis, with the possibility to detect extra-oral causes, which often remain undetected unless characterized by a specific smell.